2015
DOI: 10.1155/2015/354168
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Liver Abscess withDesulfovibrio desulfuricansBacteremia

Abstract: Desulfovibrio spp. are gram-negative, sulfate-reducing, and anaerobic bacteria found in the digestive tract of humans. Because Desulfovibrio spp. are infrequent causative agents of infectious diseases and are difficult to isolate and to identify from clinical specimens, the appropriate antibiotic therapy to infection with Desulfovibrio spp. has not been determined. We report the first case of liver abscess with bacteremia due to Desulfovibrio desulfuricans to show the clinical presentation and treatment. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…[43, 44] , Desulfovibrio spp . [45] , etc. have been identified as pathogens for liver abscess and sepsis.…”
Section: Resultsmentioning
confidence: 99%
“…[43, 44] , Desulfovibrio spp . [45] , etc. have been identified as pathogens for liver abscess and sepsis.…”
Section: Resultsmentioning
confidence: 99%
“…Desulfovibrio fairfieldensis has been isolated from the blood of a patient suffering from perforating appendicitis (Loubinoux, Mory, Pereira, & Le Faou, 2000), while D. desulfuricans together with Eggerthella lenta was indicated as the cause of a polymicrobial bloodstream infection (Liderot, Larsson, Boräng, & Ozenci, 2010). A monobacterial bacteraemia resulting from a liver abscess was found to be due to D. desulfuricans (Koyano et al, 2015).…”
Section: Infections and Bacteraemiamentioning
confidence: 99%
“…Figure 3 summarizes the association of SRB with diseases. In addition, several case studies have reported D. desulfuricans bacteremia under different clinical conditions [ 69 , 70 , 71 ]. Some studies have highlighted the effects of probiotic and prebiotic treatments on SRB population in the gut.…”
Section: Impact Of Srb Bacterial Derived H 2 Smentioning
confidence: 99%